The Legal Framework for the Protection of Turtles as Protected Animals from Culinary Business Production - Cok Dian Laksmidewi (Susbtantive Justice International Journal of Law, 2022)
Turtles are protected animals, regulated both in international agreements and by Government Regulation of the Republic of Indonesia Number 7 of 1999 on the Preservation of Plant and Animal Species. Six of seven species of turtles that still exist are in Indonesia. Protection of these animals has to deal with conditions in which their meat and eggs are still used as culinary products. Consumption of turtles is still a culture of society. The high demand for dishes made from turtles causes them to be traded illegally. In this study, the legal framework for the protection of turtles as endangered species and turtle ecotourism policies based on local wisdom will be studied. This research is empirical legal research that examines the application of the legal framework to protect turtles as protected endangered species. This research also examines the legal culture of the people who actually use turtles as a culinary business product. The data used consists of primary and secondary data. Primary data comes from interviews with criminal law experts, while secondary data consists of primary and secondary legal materials. The legal materials are collected through literature study. The legal framework for protecting turtles as endangered species is carried out by bringing this issue into international forums. A number of international agreements have been reached by countries to protect endangered animals. The Union for Conservation of Nature and Natural Resources (IUCN) even issued a Red List and put turtles on the list. The Indonesian government ratifies international legal instruments and develops policies at the national level to protect sea turtles. In addition, the government also raises public awareness not to consume turtles with a local wisdom approach